2019
DOI: 10.1021/acs.jafc.9b04522
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Delivery System Assembled by a Nanostructured Peptide Derived from the Sea Cucumber Ovum

Abstract: In this study, the binding mechanism, morphological, and conformational analysis of the complex of a sea cucumber ovum derived octapeptide (EDLAALEK) with Ca2+ as well as its calcium delivery behavior via the gastrointestinal (GI) tract were investigated. The Ca2+ specifically bound to two carboxyl oxygen atoms of C-terminal Glu and Asp on the EDLAALEK peptide at a stoichiometric ratio of 1:1. Calcium coordination induced the self-assembly of the EDLAALEK peptide, resulting in the formation of a nanocomposite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…The dissociation constant ( K d ) between DTDSEEEIR and iron was estimated to be 3.58 ± 1.26 × 10 –4 M –1 , and the association constant ( K a ) was 2.79 × 10 3 M at 25 °C. The similar value of K a was also observed for food protein-derived peptides like DHTKE (1.00 × 10 3 M), , NDEELNK (3.72 × 10 3 M), and EDLAALEK (8.59 × 10 3 M), which can serve as ligands for metal ions. This intermediate binding constant implied that iron might be released easily from the DTDSEEEIR–iron complex .…”
Section: Resultssupporting
confidence: 72%
“…The dissociation constant ( K d ) between DTDSEEEIR and iron was estimated to be 3.58 ± 1.26 × 10 –4 M –1 , and the association constant ( K a ) was 2.79 × 10 3 M at 25 °C. The similar value of K a was also observed for food protein-derived peptides like DHTKE (1.00 × 10 3 M), , NDEELNK (3.72 × 10 3 M), and EDLAALEK (8.59 × 10 3 M), which can serve as ligands for metal ions. This intermediate binding constant implied that iron might be released easily from the DTDSEEEIR–iron complex .…”
Section: Resultssupporting
confidence: 72%
“…The peptides with low molecular weight could favor calcium-binding peptides [26]. In addition, several peptides rich in acidic amino acids have been demonstrated to exert positive contributions for calcium chelation [49,50]. Values are given as the mean ± SD.…”
Section: Calcium-binding Capacity Analysismentioning
confidence: 99%
“…A peptide (EDLAALEK) derived from sea cucumber eggs was shown to have a superior CaBC. FTIR spectra showed a shift from 3432 cm −1 to 3419 cm −1 for the corresponding N-H vibrations, indicating that the amino nitrogen atom may have acted as a calcium binding site [ 73 ]. Wu et al found that new bands with wave numbers of 555.07 cm −1 appeared following the binding of the peptide to calcium as a result of the stretching vibrations of N-Ca [ 13 ].…”
Section: Calcium Binding Sites On Peptidesmentioning
confidence: 99%